A fractional model for the COVID-19 pandemic: Application to Italian data. Issue 5 (3rd September 2021) - Alòs, Elisa; Mancino, Maria Elvira; Merino, Raúl; Sanfelici, Simona
Abstract: We provide a probabilistic SIRD model for the COVID-19 pandemic in Italy, where we allow the infection, recovery and death rates to be random. In particular, the underlying random factor is driven by a fractional Brownian motion. Our model is simple and needs only some few parameters to be calibrated.